The Effective manager - Andres, Tomas D. (Quezon City, Philippines : New Day Publishers, 1995)
Faced with the urgent need for management education to empower mangers, supervisors, and executives towards effectiveness and efficiency., this book has been written to teach, integrate, and infuse the proper knowledge, attitudes, skills, habits, and values (KASHV) to all present and future people who will be managing people to attain organizational, national, as well ad personal and family objectives.
Part I. the effective manager --Part II. effective planning -- Part III. effective organizing -- Part IV. effective executions of plans -- Part. V effective managerial leading -- Part VI. effective controlling.
Includes bibliographical references.
Keywords: LEADERSHIP